Using Administrative Data to Evaluate the Effectiveness of Home Visiting Programs for Improving the Well-Being of First Nations Children and Parents - Mariette Chartier (International Journal of Population Data Science, 2018)
Introduction The province-wide Families First Home Visiting Program (FFHV) provides home visiting to families with children living in conditions of risk. It remains unknown if First Nations families are benefiting from the program. Using existing administrative and population-wide data is an innovative practice to evaluate programs that have been scaled up.